Penguatan Pendidikan Karakter melalui Pembiasaan Akhlak Terpuji dalam Pendidikan Islam: Kajian Literatur - Dini Sekar Arum; Eriska Aprilia; Taiba Husniya; Mohammad Syaifuddin (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2026)
This study aims to examine how the practice of good morals in Islamic education can improve character education. To achieve this goal, this study used a qualitative descriptive literature review method. Data were drawn from relevant books, journals, and previous research. The results show that character education in Islam focuses on the formation of noble morals through the practice of religious values, discipline, responsibility, and social concern. The practice of good morals is considered effective in shaping positive student behavior through routine activities and the role models of teachers and parents. However, its implementation faces challenges in the form of the influence of technology, social media, and a lack of cooperation between schools and families. Therefore, the practice of good morals needs to be consistently implemented in educational environments.